Analysis of the use of yakuwarigo in the drama ‘barakamon’ (a sociolinguistic study) - Andi Hanifah Zahra (Universitas Cokroaminoto Palopo, 2025)
The abstract is a summary of the article. It comprises the research objective, methods, principal results, and significant conclusions. Implications or recommendations can be added in the abstract. The abstract must be written in English and/or Indonesian and be less than 250 words. Abstracts in Indonesian are optional, especially for writers who do not use Indonesian as their native language. The abstract must not contain lengthy background information and have no reference to figures, tables, equations, or any bibliographical reference, either coming within or from another article. The language of the abstract must be clear and concise. It is a stand-alone summary in one paragraph. Immediately after the abstract, provide a maximum of 6 keywords, avoiding general and plural terms and multiple concepts (avoid, for example,